Anti-Inflammatory Effects of Fatty Acid Amide Hydrolase Inhibition in Monocytes/Macrophages from Alzheimer’s Disease Patients - Chiurchiù, Valerio; Scipioni, Lucia; Arosio, Beatrice; Mari, Daniela; Oddi, Sergio; Maccarrone, Mauro (Biomolecules (Basel, Switzerland), 2021)
Growing evidence shows that the immune system is critically involved in Alzheimer’s disease (AD) pathogenesis and progression. The modulation and targeting of peripheral immune mechanisms are thus promising therapeutic or preventive strategies for AD. Given the critical involvement of the endocannabinoid (eCB) system in modulating immune functions, we investigated the potential role of the main elements of such a system, namely type-1 and type-2 cannabinoid receptors (CB1 and CB2), and fatty acid amide hydrolase (FAAH), in distinct immune cell populations of the peripheral blood of AD patients. We found that, compared to healthy controls, CB1 and CB2 expression was significantly lower in the B-lymphocytes of AD patients. Moreover, we found that CB2 was significantly lower and FAAH was significantly higher in monocytes of the same subjects. In contrast, T-lymphocytes and NK cells did not show any variation in any of these proteins. Of note, monocytic CB2 and FAAH levels significantly correlated with clinical scores. Furthermore, the pharmacological inactivation of FAAH in monocytes and monocyte-derived macrophages obtained from AD patients was able to modulate their immune responses, by reducing production of pro-inflammatory cytokines such as TNF-α, IL-6 and IL-12, and enhancing that of the anti-inflammatory cytokine IL-10. Furthermore, FAAH blockade skewed AD monocyte-derived macrophages towards a more anti-inflammatory and pro-resolving phenotype. Collectively, our findings highlight a central role of FAAH in regulating AD monocytes/macrophages that could be of value in developing novel monocyte-centered therapeutic approaches aimed at promoting a neuroprotective environment.